Ipilimumab and Nivolumab exertes cardiotoxic and pro-fibrotic effects in mice through the overexpression of NLRP3 inflammasome, chemokines and leukotrienes. (14th October 2021) - Quagliariello, V; Passariello, M; Rea, D; Barbieri, A; Buccolo, S; Iovine, M; Bonelli, A; Caronna, A; Botti, G; De Lorenzo, C; Maurea, N
Abstract: Background: Several strategies based on immune checkpoint inhibitors (ICIs) have been developed for cancer therapy, opening to advantages in cancer outcomes. However, several ICIs-induced side effects emerged in these patients, especially a rare but clinically significant cardiotoxicity with high rate of mortality. Purpose: We studied cytotoxic and pro-inflammatory properties of Ipilimumab and Nivolumab in cellular and preclinical models Methods: Co-cultures of human cardiomyocytes and hPBMCs were exposed to Ipilimumab or Nivolumab at 100 nM; cell viability and expression of leukotrienes, NLRP3 inflammasome, MyD88 (myddosome) and p65/NF-kB were performed. C57 mice were untreated (Sham; n=6) or treated with Ipilimumab (IPI, n=6) (15 mg/kg); analysis of fractional shortening, ejection fraction, radial and longitudinal strain were made before and after treatments through 2D-echocardiography (Vevo 2100). Expression of NLRP3, MyD88, p65/NF-kB, leukotrienes and 12 cytokines (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL17-α, IFN-γ, TNF-α, G-CSF, and GM-CSF) have been analyzed in murine myocardium. Results: Nivolumab and Ipilimumab induced cell death and apoptosis in cardiomyocutes. Both ICIs increased NLRP3, MyD88 and p65/NF-kB expression compared to untreated cells, however the most pro-inflammatory and cardiotoxic effects were seen after exposure to Ipilimumab. Mice treated with Ipilimumab showed a significant decrease of fractional shortening and radial strain compared to untreated mice. Metabolic studies clearly indicates that ipilimumab increases leukotrienes production and NLRP3 expression in heart tissues, probably due to increased iROS content (iROS are key inductors of leukotrienes expression). High expression of IL-6, IL-1 and IL-17 were also seein in mice treated with ipilimumab (p<0, 001). Conclusions: Nivolumab and Ipilimumab exert cytotoxic effects mediated by NLRP3 inflammasome, leukotrienes and pro-inflammatory cytokines in heart tissues. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministero della Salute, Ricerca Corrente Project